First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations Industrial Hygiene and Human side of Industry, Commerce and Occupational Careers Prof. E. COLLIS, M.D., M.R.C.P., Professor of Preventive Medicine, University College of S. Wales & Monmouthshire Dr. LEONARD HILL, M.D. F.R.S. ROBERT R. HYDE, Director of the Industrial Welfare Society Dr. G.H. MILES, D.Sc., Assistant Director and Secretary, National Institute of Industrial Psychology Prof. C.S. MYERS, M.D., Sc.D., F.R.S., Director of the National Institute of Industrial Psychology Sir THOMAS OLIVER, M.D., LL.D., F.R.C.P., Professor of Medicine in the University of Durham The Series of Lectures, and Single Lectures, can be delivered to organisations in all parts of the Country, the terms for which are by arrangement ; travelling and out-of-pocket expenses, however, in almost every case would have to be met. COURSES OF LECTURES DELIVERED BY THE LEAGUE The SIMS WOODHEAD Series at Morley Hall, George Street, Hanover Square, Series of 13 Constructive Educational Health Lectures. Feb. 9th, 1921. "Anatomy and Physiology of the Human Body," Sir SIMS WOODHEAD. Feb. 16th, 1921. "Anatomy and Physiology of the Human Body," continued. Prof. WILSON. Feb. 23rd, 1921. "Brain and Heart." A.B. APPLETON, M.R.C.S., L.R.C.P. March 2nd, 1921. "Blood Vessels." Sir SIMS WOODHEAD. March 9th, 1921. "Food," F.H. CRIPPS, M.B. March 16th, 1921. "Organs that Supply Digestive Juices." F. H. CRIPPS, M.B. April 6th, 1921. "The Removal of Effete Matter." F.H. CRIPPS, M.B. April 13th, 1921. "Lymphatics and Lymphatic Glands." April 20th, 1921. "Water, Fresh Air — Essentials of Ventilation." J.E. PURVIS, M.A. April 27th, 1921. "Growth and Development." W. S. ROWNTREE, B.Sc. May 4th, 1921. "Adult Life." W.S. ROWNTREE, B.Sc. May 11th, 1921. "Recent Advances in our knowledge of Nutrition." W. E. DIXON, M.D. May 18th, 1921. "Decay — Natural. Premature Decay a Disease." Sir SIMS WOODHEAD. Course delivered to the L.C.C. Teachers given at London Day Training College, Southampton Row, London, W.C.1, beginning 13th October. Oct. 13th, 1921. Introductory: — "The Human Body, a Delicate but most Efficient Piece of Machinery." Sir G. SIMS WOODHEAD, K.B.E., LL.D., M.D., F.R.C.P. Oct. 20th, 1921. "Health and its Relation to Vocational Guidance." Prof. E. COLLIS, M.A., M.D., M.R.C.P., M.R.C.S. Oct. 27th, 1921. "Crime and Delinquency in Relation to Heredity, Environment and Disease." W. A. POTTS, M.A., M.R.C.S., L.R.C.P. Nov. 3rd, 1921. "Ventilation and Respiration." LEONARD HlLL, M.B., F.R.S. Nov. 10th, 1921. "Principles of Diet." ERIC PRITCHARD, M.A., M.R.C.P. Nov. 17th, 1921. "Recreation and Physical Exercise." E. B. TURNER, F.R.C.S., L.R.C.P. Nov. 24th, 1921. "The Economy of Motion." E. FARMER, M.A. (Industrial Fatigue Board). Dec. 1st, 1921. "Lighting and the Physiology of the Eye." BISHOP HARMAN, M.A., F.R.C.S. Dec. 8th, 1921. "Natural Capacity and Health in Regulation to a Career. C.J. BOND, C.M.G., F.R.C.S. Dec. 14th, 1921. "The Mental Reaction of Children as an Index of Physical Health." Sir MAURICE CRAIG, C.B.E., M. A., M.D., F.R.C.P. Special Course delivered at The Royal Society of Arts, John Street, Adelphi, London. "The Mind and what we ought to know about it." Feb. 6th, 1922. "Primitive Instinct." Dr. BERNARD HART. Feb. 13th, 1922. "Sensation, Perception, Ideation and Attention. R. H. COLE, F.R.C.P. Feb. 20th, 1922. "Association of Ideas, Recognition and Memory." R. S. Rows. M.R.C.S., L.R.C.P. 13 200/B/3/2/C693/1/71